2021
DOI: 10.1001/jamapediatrics.2020.5653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enteral Lipid Supplement on Severe Retinopathy of Prematurity

Abstract: Key Points Question Does enteral fatty acid supplementation with arachidonic acid (AA) and docosahexaenoic acid (DHA) from birth to 40 weeks’ postmenstrual age reduce severe retinopathy of prematurity (ROP) in extremely preterm infants? Findings This randomized clinical trial found that enteral AA and DHA supplementation lowered the risk of severe ROP by 50%. In addition, the group that received enteral AA and DHA supplementation showed higher serum levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(114 citation statements)
references
References 43 publications
(76 reference statements)
3
101
1
Order By: Relevance
“…Another interesting finding in our meta-analysis is that early high IVLE showed a favored effect on the incidence of ROP. A recently published RCT reported that enteral arachidonic acid and docosahexaenoic acid supplementation lowered the risk of severe ROP by 50% [33], which is in line with our meta-analysis results. One possible explanation of this result is that infants with early high IVLE might receive an additional source of long-chain polyunsaturated fatty acids in the early postnatal period, and fatty acids could be used for retinal development.…”
Section: Discussionsupporting
confidence: 92%
“…Another interesting finding in our meta-analysis is that early high IVLE showed a favored effect on the incidence of ROP. A recently published RCT reported that enteral arachidonic acid and docosahexaenoic acid supplementation lowered the risk of severe ROP by 50% [33], which is in line with our meta-analysis results. One possible explanation of this result is that infants with early high IVLE might receive an additional source of long-chain polyunsaturated fatty acids in the early postnatal period, and fatty acids could be used for retinal development.…”
Section: Discussionsupporting
confidence: 92%
“…The Mega Donna Mega study compared the outcomes of enteral supplementation with the nutritional oil Formulaid (Martek Biosciences Corporation), which provided 100 mg/kg/d of AA and 50 mg/kg/d of DHA (2:1 AA to DHA intervention group), vs no supplementation (control group) from within 3 days after birth to a postmenstrual age (PMA) of 40 weeks for severe ROP and other morbidities. Details regarding the study group, design, methods, and primary and secondary results of the Mega Donna Mega study were described by Hellström et al 13…”
Section: Methodsmentioning
confidence: 99%
“…12 Accordingly, in the multicenter Mega Donna Mega study, infants who received both AA and DHA by enteral administration from birth up to a term-equivalent age had less than half the frequency of severe ROP than infants who did not receive supplementation. 13 We hypothesized that higher mean daily DHA and AA levels were associated with less severe ROP. Specifically, in this cohort study, we aimed to assess whether ROP severity is associated with serum levels of LC-PUFA, especially DHA and AA and their interaction, during the first 28 postnatal days.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of long-chain polyunsaturated fatty acids, particularly the n-3 fatty acid DHA and n-6 fatty acid arachidonic acid (AA), for preterm infant health and development is becoming increasingly recognized. It was recently reported that enteral supplementation with an oil enriched in DHA and AA to extremely preterm infants lowered the risk of developing severe ROP by more than 50% [ 20 ]. In this study, we observed a dramatic decrease in the fraction of PC species in serum containing AA and DHA during the first postnatal week.…”
Section: Discussionmentioning
confidence: 99%
“…While RBCs are the major contributor to S1P plasma levels, a considerable fraction of the S1P found in serum is derived from activated platelets and is released in response to coagulation after blood sampling [ 17 ]. S1P synthesis is stimulated by the omega-3 long-chain polyunsaturated fatty acid docosahexaenoic acid (DHA) [ 18 ], which in turn has been shown to protect against ROP [ 19 , 20 ]. Phosphatidylcholine (PC) is the main carrier of DHA in the blood of preterm infants [ 21 ].…”
Section: Introductionmentioning
confidence: 99%